Screening of fungicides and plant extracts for controlling blight disease of Tagetes spp. - Akhter, Mahfuza; Shamsi, Shamim (Journal of the Asiatic Society of Bangladesh, Science, 2021)
A field experiment was conducted in the Botanical research garden, Department of Botany, University of Dhaka during 2015, 2016 and 2017 to evaluate the efficacy of two fungicides and two plant extracts against blight disease of Tagetes erecta L. and T. patula L. Both the fungicides Bavistin 50 WP and Tilt 250 EC and leaf extracts of Azadirachta indica A. Juss. and Citrus medica L. showed effective management of the disease over the untreated check. However, among the treatments, Bavistin 50 WP and Tilt 250 EC at 100 ppm concentration and A. indica and C. medica L. at 10% concentration were found significantly superior in controlling percent disease index and increasing number of healthy flowers. The number of healthy flowers was highest per plant, 17.13 in T. erecta in 2017 and 25.00 in T. patula in the year 2016. J. Asiat. Soc. Bangladesh, Sci. 47(1): 79-89, June 2021